2018
DOI: 10.1038/s41380-018-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain scans from 21,297 individuals reveal the genetic architecture of hippocampal subfield volumes

Abstract: The hippocampus is a heterogeneous structure, comprising histologically distinguishable subfields. These subfields are differentially involved in memory consolidation, spatial navigation and pattern separation, complex functions often impaired in individuals with brain disorders characterized by reduced hippocampal volume, including Alzheimer’s disease (AD) and schizophrenia. Given the structural and functional heterogeneity of the hippocampal formation, we sought to characterize the subfields’ genetic archite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
106
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 76 publications
13
106
0
Order By: Relevance
“…It is also possible, however, that hippocampal volume and WM microstructure are independently impacted by stressrelated mechanisms including glutamate excitotoxicity, inflammation, oxidative stress or an increase in glucocorticoids. Recent imaging genetics studies also suggest that a genetic predisposition to such neuroanatomical variations may also be related to the genetic underpinnings of mental illness [54].…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible, however, that hippocampal volume and WM microstructure are independently impacted by stressrelated mechanisms including glutamate excitotoxicity, inflammation, oxidative stress or an increase in glucocorticoids. Recent imaging genetics studies also suggest that a genetic predisposition to such neuroanatomical variations may also be related to the genetic underpinnings of mental illness [54].…”
Section: Discussionmentioning
confidence: 99%
“…By searching GWAS catalog [1], we found that three out of six (METTL10, LEMD3, and MYLK2) genes were reported to be associated with volume related IDPs. For example, METTL10 was associated with mean platelet volume [28], total hippocampal volume [29], and dentate gyrus granule cell layer volume [29]. STX6 was identified by all three mapping strategies and contained a significant SNP (rs3789362) with CADD score higher than 20.…”
Section: Functional Annotation Of Genetic Variantsmentioning
confidence: 99%
“…41 The association between snoring genes and heel bone mineral density could be mediated by BMI due to the association between BMI and bone density documented previously. 42 MSRB3 plays a relevant role in protein and lipid metabolism pathways 43 and has been associated with hippocampal volume, [44][45][46] lung function, 40,47,48 Alzheimer's disease, 49,50 brain injuries, 51 novelty seeking, 52 deafness 53 and height. 40 These results could be consistent with the fact that severe snoring may incur in nocturnal oxygen desaturation, 54 diminishing neuropsychological functions and in some cases, resulting in tissue damage 55 and contributing to impairment of memory consolidation processes.…”
Section: Discussionmentioning
confidence: 99%